Correlations Between Dispersive Alfvén Wave Activity, Electron Energization, and Ion Outflow in the Inner Magnetosphere. Issue 17 (27th August 2020) - Hull, A. J.; Chaston, C. C.; Bonnell, J. W.; Damiano, P. A.; Wygant, J. R.; Reeves, G. D.
Abstract: Using measurements from the Van Allen Probes, we show that field‐aligned fluxes of electrons energized by dispersive Alfvén waves (DAWs) are prominent in the inner magnetosphere during active conditions. These electrons have preferentially field‐aligned anisotropies from 1.2 to >2 at energies ranging from tens of electron volts to several kiloelectron volts (keV), with largest values being coincident with magnetic field dipolarizations. Comparisons reveal that DAW energy densities and Poynting fluxes are strongly correlated with precipitating electron energies and energy fluxes and also O + ion outflow energies. These observations yield empirical inner magnetosphere relations between the DAW and electron inputs and the O + ion outflow response, providing important constraints for models. They also suggest that DAWs play an important role in enhancing field‐aligned electron input into the ionosphere that facilitates the outflow and subsequent energization of O + ions in the wave fields into the inner magnetosphere. Plain Language Summary: We use satellite observations in the inner magnetosphere to study field‐aligned electrons at kiloelectron volt energies and below. These electrons are invariably coincident with intense low‐frequency electromagnetic waves called dispersive Alfvén waves (DAWs), which are prevalent during substorms and geomagnetic storms. Given that DAWs have parallel electric fields known to accelerate electrons, their simultaneous occurrences indicate that these waves are accelerating the electrons in the equatorial inner magnetosphere. Indicative of energization and heating in DAWs, the energies, number fluxes and energy fluxes of earthward‐moving electrons are observed to increase with increasing DAW Poynting fluxes and energy densities. Given the ability of electron precipitation and DAWs to drive and produce energized ion outflow, we also tested for and demonstrated that oxygen ion outflow energies are strongly correlated with the electron and wave energy fluxes. Least squares fits yielded empirical relationships between the DAW, electron, and oxygen ion outflow characteristics, providing important constraints for models of plasma transport in the magnetospheric‐ionospheric system. Owing to their persistent occurrence during active conditions and field‐aligned sense, these wave energized electrons are expected to affect the growth and spatial distribution of other waves known to impact inner magnetosphere source and loss processes. Key Points: Inner magnetosphere field‐aligned electron fluxes and dispersive Alfvén waves are strongly enhanced during storms and substorms Field‐aligned electron energy and energy fluxes are strongly correlated with dispersive Alfvén wave energy densities and Poynting fluxes Oxygen ion outflows show strong correlations with field‐aligned electron precipitation and dispersive Alfvén waves